1997
DOI: 10.2172/495695
|View full text |Cite
|
Sign up to set email alerts
|

Predicting weld solidification cracking using damage mechanics -- LDRD summary report

Abstract: This report summarizes the efforts to develop and validate a finite element based model to predict weld solidification cracking behavior. Such a model must capture the solidification behavior, the thermal behavior in the weld pool region, the material mechanical response, and some failure criteria to determine when solidification cracking will occur. For such a program to be successful, each aspect of the model had to be accurately modeled and verified since the output of one portion of the model served as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Some researchers have indicated that the latent heat of fusion highly influences the shape and size of the weld pool, as well as the temperature distributions in the vicinity of the weld pool. Dike et al [27] and Brooks and Dike [28] evaluated three different latent heat release models. They obtained quite a good agreement with measured strains and temperatures.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…Some researchers have indicated that the latent heat of fusion highly influences the shape and size of the weld pool, as well as the temperature distributions in the vicinity of the weld pool. Dike et al [27] and Brooks and Dike [28] evaluated three different latent heat release models. They obtained quite a good agreement with measured strains and temperatures.…”
Section: Heat Transfer Modelmentioning
confidence: 99%